Foreword - Zigmunde, Alīda (History of Engineering Sciences and Institutions of Higher Education, 2018)
The second volume of the scientific journal of RTU Research Centre for Engineering History (RCEH) is devoted to the 100th anniversary of the Republic of Latvia. The authors of articles are historians of science, pedagogues and museum workers of Latvia, Lithuania and Ukraine. The themes of articles and their main characters are related to the Riga Polytechnicum (RP) / Riga Polytechnic Institute (RPI).